ISOLATION OF PROBIOTIC BACTERIA FROM NON-DAIRY PRODUCTS : A NEW APPROACH IN FUNCTIONAL FOODS FOR LACTOSE INTOLERANCE (CAHIERS MAGELLANES-NS, 2024)
Individuals with lactose intolerance often seek dairy-free alternatives for pro-biotic consumption. This study aimed to isolate pro-biotic bacteria from non-dairy sources suitable for lactose-intolerant and vegan individuals. Non-dairy foods which include idly and dosa batter were screened for potential pro-biotic strains using selective media and molecular identification techniques. Bacterial isolates were evaluated for basic tests againt pro-biotic characteristics such as acid and bile tolerance. A total of 25 samples were isolated from the selected food samples. From which potential pro-biotic strains were isolated and identified, including Lactobacillus plantarum, Lactobacillus fermentum and Bacillus mojavensis known for their beneficial effects on gut health. Further studies are warranted to assess the efficacy of these non-dairy derived pro-biotics in alleviating symptoms of lactose intolerance and improving overall gut microbiota composition in human trials. This research highlights the potential of non-dairy sources as viable alternatives for pro-biotic delivery, catering specifically to lactose-intolerant individuals.